2023
DOI: 10.1097/bot.0000000000002602
|View full text |Cite
|
Sign up to set email alerts
|

Where Are We in 2022? A Summary of 11,000 Open Tibia Fractures Over 4 Decades

Abstract: Objectives: To determine the infection and nonunion rates for open tibia fracture treatment over the past 4 decades since the introduction of the Gustilo–Anderson (GA) open fracture classification. Data Sources: PubMed, Scopus, CINAHL, and Cochrane databases were reviewed using the PRISMA checklist for articles between 1977 and September 2018. Study Selection: One hundred sixty-one articles meeting the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 160 publications
(314 reference statements)
0
5
0
Order By: Relevance
“…The highest incidence of infection amongst these trials was conducted in Uganda 37 which included a higher rate of patients with Gustilo Anderson III fractures, which are known to be associated with higher rates of infection. 38,39 Large prospective observational studies in LMICs have shown a low rate of infection following operative management of people with fractures. 18 The high incidence of infection reported in our one selected article may be due to the increasing incidence of severe fractures, delays in operative management or availability of plastic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…The highest incidence of infection amongst these trials was conducted in Uganda 37 which included a higher rate of patients with Gustilo Anderson III fractures, which are known to be associated with higher rates of infection. 38,39 Large prospective observational studies in LMICs have shown a low rate of infection following operative management of people with fractures. 18 The high incidence of infection reported in our one selected article may be due to the increasing incidence of severe fractures, delays in operative management or availability of plastic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in antibiotic therapy, debridement, and fixation strategies, the numbers remain largely unchanged. 5 Gustilo et al 6 A progressively worsening prognosis was seen within these subtypes as IIIA injuries had a 4.4% infection rate with no amputations, IIIB injuries had a 52% infection rate with 16% leading to amputation, and IIIC injuries had a 42% infection rate with a 42% amputation rate. Over time, there have been numerous attempts to modify the Gustilo classification.…”
Section: History Of Current Classification Systemsmentioning
confidence: 99%
“…Despite advances in antibiotic therapy, debridement, and fixation strategies, the numbers remain largely unchanged. 5 Gustilo et al 6 further subclassified type III open fractures into IIIA: open fractures with adequate soft-tissue coverage of a fractured bone despite extensive soft-tissue laceration or flaps or high-energy trauma regardless of the size of the wound; IIIB: open fractures with extensive soft-tissue injury loss with periosteal stripping and bone exposure, which are usually associated with massive contamination; and IIIC: open fractures associated with arterial injury requiring repair. A progressively worsening prognosis was seen within these subtypes as IIIA injuries had a 4.4% infection rate with no amputations, IIIB injuries had a 52% infection rate with 16% leading to amputation, and IIIC injuries had a 42% infection rate with a 42% amputation rate.…”
Section: History Of Current Classification Systemsmentioning
confidence: 99%
“…Advances in fracture fixation, soft-tissue management, and antimicrobial therapy have significantly improved treatment options for patients. 14 Institutional algorithms and protocols for treating open tibia fractures, and open fractures in general, should be developed on evidence-based recommendations. We aim to briefly summarize the key, evidence-based interventions, which improve outcomes and prevent infection and osteomyelitis after open tibia fractures.…”
Section: Prevention: a Systematic Approachmentioning
confidence: 99%